The Influence of Discipline and Environment on Students’ Learning Creativity in The Field of Study Integrated Social Sciences Spatial Interaction Material In Life In Asean Countries of SMP 5 Padangsidempuan - Yusmiati, Yusmiati; Kausar Daulay; Mira Sahrida (International Journal of Educational Research Excellence (IJERE), 2026)
The formulation of the problem in this study is whether discipline and environment influence the learning creativity of students in the field of integrated social studies on the material of spatial interaction in life in ASEAN countries at SMP Negeri 5, Padangsidimpuan. The objective of this study is to determine the influence of discipline and environment on the learning creativity of students in the field of integrated social studies on the material of financial interaction in life in ASEAN countries. The type of research that the author used in this study was sociative. The questionnaire was used as a data-collection tool. Based on data analysis, a known r count of 0.998 was obtained. While the r table has a confidence level of 95% or an error rate of 5% with N=30 as big as 0.361 with thus can known that mark The calculated r is greater than the table r value, namely (0.998> 0.361). Thus, It can be said that Ha is accepted that discipline and environment influence the learning creativity of students in the Integrated Social Studies study field of spatial interaction material in life in ASEAN countries in class VII of SMP Negeri 5 Padangsidimpuan